Situation report on Nepal’s agrifood systems: May 2024 - Palikhe, A.; Maharjan, N.K.; Gupta, S.; Adhikari, M.; Kumar, A.; Minot, Nicholas; Koirala, Pankaj; Krupnik, Timothy J. (CSISA, 2024)
In April 2024, Nepal saw a 1.8 percent increase in the prices of food and beverages compared to the previous month. During the same period, the year-on-year inflation rate for food and beverages reached 5.2 percent, surpassing the overall consumer inflation rate of 4.6 percent. The main contributors to the rise in food prices in April were the annual spikes in the prices of spices (22.6 percent) and vegetables (17.0 percent). Moreover, staple food items such as cereal grains, pulses, and legumes also experienced significant price hikes over the course of the year. Food price inflation was highest in the Terai region (5.6 percent) and lowest in the Mountain districts (3.2 percent).